Establishment and maintenance of sand fly colonies - Volf, P; Volfova, V (Journal of vector ecology, 2011)
Sand flies used to have a reputation for being difficult and labour-intensive to breed. Here we summarize our experience with establishment and maintenance of sand fly colonies and their use for infective experiments: techniques for collection and handling wild-caught females, rearing larvae and adults and experimental infections of sand flies by Leishmania using membrane feeding. In addition, we compare major life cycle parameters between various colonies maintained under standard laboratory conditions. The sand fly rearing is tricky but some species can be reared in large numbers with a minimum of space and equipment. Initiation of new colonies from endemic sites is a prerequisite for accurate studies on parasite-vector interaction but it is more difficult step than routine maintenance of colonies already established in laboratory for many generations.
Keywords: Insect Vectors; Mice; Phlebotomus; Female; Leishmania; Animals; ženské pohlaví; hmyz - vektory; zvířata; myši